2023
DOI: 10.3390/infrastructures8020023
|View full text |Cite
|
Sign up to set email alerts
|

Examination of Concrete Canvas under Quasi-Realistic Loading by Computed Tomography

Abstract: The current paper concerns the investigation of CC (Concrete Canvas), a unique building material from the GCCM (geosynthetic cementitious composite mat) product group. The material is suitable for trench lining, trench paving, or even military construction activities, while the authors’ purpose is to investigate the application of the material to road and railway substructure improvement. This research was carried out to verify the material’s suitability for transport infrastructure and its beneficial effects.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…In [19], it was proved that the CC layer is not punctured in this layer structure under this amount of loading (Fig. 3).…”
mentioning
confidence: 83%
See 3 more Smart Citations
“…In [19], it was proved that the CC layer is not punctured in this layer structure under this amount of loading (Fig. 3).…”
mentioning
confidence: 83%
“…On the other hand, this GCCM technology could also ensure increasing ballast stability. In [19], the authors showed that ballast under loading can be pressed into the CC material, which means that the bottom layer of ballast is cemented into the layer which increases the inner shear resistance, as well as the case when geogrids are used. From this aspect, one of the aims of this article is to compare the behaviors and technical effects of geogrids in railway track structures.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, this prevents the necessity for conventional procedures such as blending, molding, and extracting (Li et al, 2019). The applications of this material vary from in atable tents and ditch lining to slope protection, building restoration, and reinforcement (Ding et al,2020;Jafari et al, 2020;Ding et al,2022;Liu et al, 2023;Eller et al, 2023;Xiang et al, 2023. In comparison to traditional materials used for slope protection layers, such as shotcrete layers, GCCMs offers easier, and more costeffective installation process, providing substantial bene ts like reduced environmental impact, shortened construction periods, and lower labor costs. Furthermore, it is effectiveness in rapidly constructing slope protection, such as emergency slope protection or heavy rainfall (Li et al 2016;Zhang 2020).…”
Section: Introductionmentioning
confidence: 99%